(untitled) (Herald of Journalism, 2019)
The oeuvre of the great scientist, poet, philosopher, mathematician, astronomer, astrologer Omar Khayyam arouses the enduring interest of researchers. Each direction of science is aimed at the cognition of the world, to which the oriental sage has devoted his life to solving the mystery. The purpose of the article is to analyze the scientific, philosophical and literary heritage of the scientist, his educational contribution to the world’s cultural treasury. The authors determine the place and role of the creative heritage of Omar Khayyam in the modern world by investigating historical sources which describe facts about the life and work of a scientist. The article contains a multi-level research concept, and they are not reducible to simplified schemes of the scientist’s life and career. Studying the multidimensionality of the phenomenon of Omar Khayyam in literature, history, philosophical and his educational tractates, the authors of this article note the multipolarity of scientific approaches and interpretations of the Rubaiat. The personality of Omar Khayyam ranks with the great names of Rudaki, Ferdowsi, Sanai, Jami, Saadi, Hafiz, Rumi and other philosophers. He was called as the most educated person of the century, a connoisseur of truth, the king of hilosophers of the East and West. The authors also analyze the original writing style of Omar Khayyam, filled with “pessimistic” humor, cosmic meaning, and also analyze texts reflecting the life and creative changes in the fate of the poet. For many centuries, he was known as a famous mathematician, astronomer and physicist, but only in the XIX century the publication of European translations of his poetic lines really made him a world’s famous writer.